2019
DOI: 10.1002/jcp.28517
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of head and neck squamous cell carcinoma survival based on the expression of 15 lncRNAs

Abstract: Recent evidence suggests that long noncoding RNAs (lncRNAs) are essential regulators of many cancer‐related processes, including cancer cell proliferation, invasion, and migration. There is thus a reason to believe that the detection of lncRNAs may be useful as a diagnostic and prognostic strategy for cancer detection, however, at present no effective genome‐wide tests are available for clinical use, constraining the use of such a strategy. In this study, we performed a comprehensive assessment of lncRNAs expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In fact, accurate prognosis, therapeutic strategy, and identification of oncogenes were encumbered by unexpected heterogeneity in HNSCC. This complex heterogeneity may signify the difficulty to accurately predict patient outcomes in tumors that have not yet metastasized, due to the resistance of certain normal-looking cells to targeted therapies or their ability to generate and promote metastasis [ 10 ]. The main purpose of immunotherapy is to eradicate cancer cells by increasing the activity of the immune system [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, accurate prognosis, therapeutic strategy, and identification of oncogenes were encumbered by unexpected heterogeneity in HNSCC. This complex heterogeneity may signify the difficulty to accurately predict patient outcomes in tumors that have not yet metastasized, due to the resistance of certain normal-looking cells to targeted therapies or their ability to generate and promote metastasis [ 10 ]. The main purpose of immunotherapy is to eradicate cancer cells by increasing the activity of the immune system [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA AC025580.2 has a positive influence on immune escape in pancreatic cancer [ 27 ]. In addition, a large number of lncRNAs have been confirmed to act as diagnostic and prognostic biomarkers or potential therapeutic targets in multiple tumors [ 11 , 28 32 ]. However, the role of immune-related lncRNAs (IRLs) in the prognostic evaluation of BC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Another report identified a 5-lncRNA based model for predicting the survival of patients with HNSCC, in which a weighted correlation network analysis was used to identify prognosis-associated lncRNAs (35). A recent study by Zhang et al (36) identified 15 prognostic lncRNAs using a differentially expressed gene analysis, in which ALMS1-IT1 was the common lncRNA and the others were different from the lncRNAs used for the construction of the predictive model. The present study utilized a robust likelihood-based survival analysis to screen for candidate lncRNAs associated with prognosis (1517,37,38) and identified a 4-lncRNA risk model, which includes lncRNAs that had not been previously reported.…”
Section: Discussionmentioning
confidence: 99%